-6u+12=-u+2

Simple and best practice solution for -6u+12=-u+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6u+12=-u+2 equation:


Simplifying
-6u + 12 = -1u + 2

Reorder the terms:
12 + -6u = -1u + 2

Reorder the terms:
12 + -6u = 2 + -1u

Solving
12 + -6u = 2 + -1u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add 'u' to each side of the equation.
12 + -6u + u = 2 + -1u + u

Combine like terms: -6u + u = -5u
12 + -5u = 2 + -1u + u

Combine like terms: -1u + u = 0
12 + -5u = 2 + 0
12 + -5u = 2

Add '-12' to each side of the equation.
12 + -12 + -5u = 2 + -12

Combine like terms: 12 + -12 = 0
0 + -5u = 2 + -12
-5u = 2 + -12

Combine like terms: 2 + -12 = -10
-5u = -10

Divide each side by '-5'.
u = 2

Simplifying
u = 2

See similar equations:

| 15x^2+36*x=31 | | -t^2-5t= | | 4ln(1/x)=1 | | 22-x=32 | | (7x)(x-4)=0 | | -t^2+2t= | | 103-2x=90 | | (4x-58)=90 | | 10x^7-14x^3/2x^3 | | -s^2-2s= | | 0.12=(x)(0.19)+(1-x)(0.08) | | -t^2-12t= | | (4x-58)=360 | | 7x2=5x-3/6 | | -a^2+15a= | | (4x-58)=369 | | 4x-58=180 | | -a^2+10a= | | (h+7)(h+3)=0 | | 0.12=(x)(0.19)+(1-w)(0.08) | | 2x-3-12/4-5 | | 90+59+x=180 | | a^2+11a= | | n^2+15n= | | 0.81h^3-h-13= | | 2x+1-x-1=1 | | 103-2x=180 | | 3x+15=21x+4 | | 103-2x=18 | | 6x+4=7x-9 | | -x^2+10x= | | -m^2-7m= |

Equations solver categories